Teacher training organisations and their preparation of the pre-service teacher to deliver comprehensive sexuality education in the school setting: a systematic literature review - O'Brien, Heidi; Hendriks, Jacqui; Burns, Sharyn (Taylor & Francis, 2020)
This study explored the extent to which organisations responsible for initial teacher training, prepare pre-service teachers to deliver comprehensive sexuality education in schools. Five electronic databases were searched to identify publications that reported the provision of CSE training for pre-service teachers. Methodological quality was appraised using The Joanna Briggs Institute Critical Appraisal Checklist for Systematic Reviews and Research Syntheses. Descriptive analyses were conducted to summarise the scope of pre-service teacher preparation. Twenty-two documents, primarily from the UK, Australia and the USA were identified for review. Overall, information regarding training in comprehensive sexuality education for pre-service teachers is limited. The review identified wide variability in training content and positioning in primary and/or secondary programmes as either core or elective requirements. Current provision does not appear to align with international and best-practice guidelines in most instances. Further research and greater transparency regarding the preparation of pre-service teachers to deliver comprehensive sexuality education is recommended to identify and prioritise best-practice holistic teaching concepts to improve teacher and student outcomes.